KESUKSESAN SISTEM TEKNOLOGI INFORMASI PADA PENERAPAN E-PROCUREMENT DI PEMERINTAH DAERAH - , SOFYAN HADINATA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to obtain empirical evidence on the success of the information technology systems that viewed from the quality of system and the quality of information on the implementation of e-procurement in local government. Success in this research refers to the use and satisfaction of users of the e-procurement system, and also give an impact on the individuals and organizations that use it. The method of research used in this study are mixed method. The population in this study are the committee procurement of goods and services in local government, while the sample are the committee procurement of goods and services electronically in the city of Yogyakarta, Bantul and Sleman regency. Data analysis tools used in this study is SmartPLS ver.2.0.M3. The result of statistic and interview shows that the quality system is a positive effect on user satisfaction. The quality of information is a positive influence on the user satisfaction, but not to actual use. While actual use is also a positive influence on the individual impact and organizational impact. In addition, user satisfaction is also making a positive impact for the individual impact.